2015
DOI: 10.1055/s-0035-1564711
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and Functional Hip Long-Term Results after Exstrophy Repair

Abstract: Introduction?Abnormalities of the bony pelvis in exstrophy-epispadias complex (EEC) and their possible relation to hip disease are well described. However, there is a lack of information about long-term orthopedic consequences and hip function in patients with EEC. Therefore, we investigated clinical and radiological results in an EEC patient cohort after long-term follow-up. Patients and Methods?We conducted a cross-sectional study using standardized radiography, clinical investigation, and the Harris hip sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 16 publications
1
11
0
Order By: Relevance
“…Kertai et al was able to show that despite BE-specific hip morphology, long-term hip function was not impaired in adult adolescent patients after symphysial approximation without osteotomy in infancy. The symphysis diastasis after this procedure was also comparable to available post-osteotomy data in the long-term (43). In a case series published by Mushtaq et al (2), primary bladder closure without osteotomy and post-operative immobilization was successful in 70 of 74 patients (95%) in respect to bladder closure.…”
Section: Need Of Osteotomiessupporting
confidence: 74%
See 1 more Smart Citation
“…Kertai et al was able to show that despite BE-specific hip morphology, long-term hip function was not impaired in adult adolescent patients after symphysial approximation without osteotomy in infancy. The symphysis diastasis after this procedure was also comparable to available post-osteotomy data in the long-term (43). In a case series published by Mushtaq et al (2), primary bladder closure without osteotomy and post-operative immobilization was successful in 70 of 74 patients (95%) in respect to bladder closure.…”
Section: Need Of Osteotomiessupporting
confidence: 74%
“…But there are also reports confirming no difference in success of bladder closure (1, 41, 42). However, it is known that symphysis diastasis recurs after all commonly used pelvic closure techniques (43). There are only a few studies dealing with pubic diastasis after various types of pelvic osteotomy in a reasonable follow-up (3639).…”
Section: Need Of Osteotomiesmentioning
confidence: 99%
“…[6][7][8][9][10]20 In contrast, persistent pubic symphysis diastasis has not been fully certified to be associated with prospective hip function in patients with EEC. 6,15,17,25,26 Sutherland et al 15 reported that pelvic osteotomy for closing the pubis does not improve gait patterns in patients with bladder exstrophy. Kantor et al 6 did not identify clear orthopaedic indications for early pubic correction osteotomy in patients with bladder exstrophy except for abdominal wall closure.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have suggested that pubic bone abnormalities in patients with EEC are potentially associated with the development of hip dysplasia including complete dislocation, requiring surgical interventions to the hip joint such as pelvic osteotomy or arthroplasty. [11][12][13][14] The incidence of hip dysplasia in patients with EEC has been reported to range widely, from 0% to 38%, [2][3][4][15][16][17] without clear descriptions about whether pubic symphysis diastasis is present. There have been no longitudinal studies of the type of pelvic abnormalities and patient characteristics associated with future hip dysplasia in patients with CDPS.…”
mentioning
confidence: 99%
“…7 Adjunctive osteotomies and closure of the symphysis are frequently used, but is a subject of debate. 8,9 Urinary diversion (UD) encompasses surgical procedures which reroute and drain urine flow from its normal pathway, and it is used as secondary treatment after failed reconstructions in incontinent or continent versions, 1 but it can also be a primary intervention with cystectomy and a continent anal diversion. 10…”
Section: Primary Surgical Treatmentmentioning
confidence: 99%